Studi lapangan variabel iklim rumah vernakular pantai dan gunung dalam menciptakan kenyamanan termal adaptif - hermawan, hermawan (Jurnal Arsitektur ZONASI, 2018)
Microclimate variables are one of the variables that affect adaptive thermal comfort. The microclimate variables are air temperature, solar radiation temperature, air humidity and wind speed. In this study the discussion of microclimate variables is specific to air temperature and air humidity. This is based on other studies which mention that the most influential climate variables are air temperature and humidity. This research is a field study that will compare air temperature and humidity in coastal and mountain areas. Measurements are carried out in 3 seasons, namely the dry season to rain, the rainy season and the rainy season to the dry season. Measurement of air and humidity temperature variables in two rooms in the building and outside space and terrace. The results of the study show that there are significant differences between coastal and mountain dwellings. This difference is related to adaptive thermal comfort through thermal sensation. Thermal sensation results show that the location of the mountain is that most residents feel cool, while at the beach location, the residents are mostly comfortable or neutral.